Higher Order Thinking Skills: The Process of Developing Questions With Kahoot Asisted - Sari Saraswati; Iesyah Rodliyah; Novia Dwi Rahmawati (Jurnal Inovasi Matematika, 2022)
This study aims to produce questions based on Higher Order Thinking Skills (HOTS) that are valid, practical, and have potential effects using Kahoot application. This research is a design research type of development study. Subject were 32 students of Mathematics Education. Data collection instruments used questionnaires and interviews. The data were analyzed descriptively using anates software version 4.0.9. This study resulted in 16 multiple choice questions on exponential and logarithmic functions, sequences and series, and trigonometry which are suitable using Kahoot application. The results showed that the developed HOTS-based questions reach the criteria of being valid, practical, and effective to support Matematics Eduaction student’ higher order thinking skills of Mathematics Education.